2022
DOI: 10.1021/acs.est.2c05625
|View full text |Cite
|
Sign up to set email alerts
|

Algal Density Controls the Spatial Variations in Hg Bioconcentration and Bioaccumulation at the Base of the Pelagic Food Web of Lake Taihu, China

Abstract: Algal density can significantly impact mercury (Hg) bioaccumulation and biomagnification in aquatic food webs, but the underlying mechanisms remain controversial especially in subtropical and tropical regions. We conducted a comprehensive field study on Hg bioconcentration in phytoplankton and bioaccumulation in size-fractionated zooplankton across 17 sampling sites in Lake Taihu, a large shallow lake in eastern China with large spatial differences in algal density. The higher algal density in the northern sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
2
4
0
Order By: Relevance
“…With a cell density of 25-fold higher, IHg T and MeHg T in the cell population with a density of 5 × 10 6 cells mL –1 were approximately 2- and 5-fold lower than those with a density of 2 × 10 5 cells mL –1 , respectively. Accordingly, the proportion of cellular MeHg contents to the total Hg contents would be higher in low-density algae populations, which agrees with observations in natural water . Besides, another trend was that at lower algal densities, higher cellular Hg contents were always accompanied by a wider mass distribution, suggesting a higher degree of intraspecies heterogeneity.…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…With a cell density of 25-fold higher, IHg T and MeHg T in the cell population with a density of 5 × 10 6 cells mL –1 were approximately 2- and 5-fold lower than those with a density of 2 × 10 5 cells mL –1 , respectively. Accordingly, the proportion of cellular MeHg contents to the total Hg contents would be higher in low-density algae populations, which agrees with observations in natural water . Besides, another trend was that at lower algal densities, higher cellular Hg contents were always accompanied by a wider mass distribution, suggesting a higher degree of intraspecies heterogeneity.…”
Section: Resultssupporting
confidence: 88%
“…Accordingly, in environmental scenarios, the cellular Hg contents would be lower in eutrophic water, further resulting in lower Hg levels in the food web. More importantly, both our laboratory results and previous field investigation found that the proportions of MeHg to total Hg on the algae negatively correlate with algal density, implying a lower transfer efficiency of MeHg in eutrophic water. Above all, validated by the experimental results, the proposed model equations can well describe the relations among m , c n , VCF, c Hg‑ini , and c Hg‑res .…”
Section: Resultssupporting
confidence: 59%
See 3 more Smart Citations